الأنا والآخر في شعر النساء في الأندلس - مصطفى, روشن عبدالستار (Sulaimani Journal for Humanities, 2021)
The Andalusian woman was distinguished by her continuous appearance in the cultural, emotional, political in the Andalusian environment. In this paper we will show the presence of Andalusian women as ego that affects and is affected by the other. Ego that have a position and ego that be reason for the change of the other, and ego that sets limits for the other, and ego that influenced by the other at the same time. The research adopted analytical approach. Also in this paper, the poetry of Andalusian women were selected. The research was categorized and analyzed to suit the research needs. The aim of the research is to show the places of (Ego) the female poet in Andalusian poetry and the Andalusian society and determine its effectiveness in the other, and the effectiveness of the other in it. It is to observe and analyze the mechanisms of this interaction by analyzing the poetic verses of (Ego) the female poet. The research included the following themes: • The theme of the presence of (Ego) and reinforcement itself. • The theme of the (Ego) and the (intimate) other or another. • The theme of the (Ego) and the far (other) or another.